2010
DOI: 10.5172/ijpl.6.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Improving English Language and Computer Literacy Skills in an Adult Refugee Program

Abstract: The study reported in this article explores ways of improving English language proficiency and computer literacy skills of adult refugees in a community program. For the adult refugee program, two main issues were considered and addressed: (1) the teaching of English as a second language (ESL) to adults with very limited English language proficiency and (2) the development of computer literacy skills of adults with no or very little computer experience. Main teaching strategies used for this focus group were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Consistent with previous research (van Rensburg & Son, 2010), this study found that the teachers at Langfield effectively embedded some aspects of digital literacies into language learning. Adding to this research knowledge, our study also found that some teaching practices for digital literacies were effective for their adult learners because they were informed by strength-based principles in connection with the affordances of material resources.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with previous research (van Rensburg & Son, 2010), this study found that the teachers at Langfield effectively embedded some aspects of digital literacies into language learning. Adding to this research knowledge, our study also found that some teaching practices for digital literacies were effective for their adult learners because they were informed by strength-based principles in connection with the affordances of material resources.…”
Section: Discussionsupporting
confidence: 90%
“…From this perspective, although people from migrant and refugee backgrounds come with incredibly varied digital experiences (Kenny, 2016), digital literacies can represent a significant challenge for anyone learning a new language (Alam & Imran, 2015;McClanahan, 2014;Smyser, 2019;van Rensburg & Son, 2010). Learners from migrant and refugee backgrounds are usually optimistic about learning digital literacies, at least initially (Gangadharan, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, it was found that prospective teachers’ tool literacy and metacognitive self-regulating capabilities had predictive effects on their attitudes towards structuring personal learning environments with Web 2.0 tools (Lim & Newby, 2021 ). There were also other studies showing a positive relationship between DL and CSE (Tour et al, 2021 ; van Rensburg & Son, 2010 ).…”
Section: Discussionmentioning
confidence: 63%
“…Most papers do not provide details on methods that would allow for reproducibility. For example, instructors cite how slow the literacy acquisition process can be without providing timelines for how long it takes students to transition from no print literacy to a beginning level of understanding text (Bigelow & Schwarz, ; Bigelow & Vinogradov, ; Burt et al, ; Haverson & Haynes, ; Shaughnessy, ; van Rensburg & Son, ). A careful and systematic documentation of learning as Warren, Fey, and Yoder (2007) have advocated for in language impaired populations is essential for the field of refugee literacy instruction if we are to begin to understand what works for whom, for what component of literacy and in what amount.…”
Section: Current Approaches To Teaching Refugeesmentioning
confidence: 99%